2013
DOI: 10.5732/cjc.012.10317
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder malignant paraganglioma with vertebral metastasis: a case report with literature review

Abstract: Paraganglioma is a rare neuroendocrine neoplasm observed in patients of all ages, with an estimated incidence of 3/1,000,000 population. It has long been recognized that some cases are familial. The majority of these tumors are benign, and the only absolute criterion for malignancy is the presence of metastases at sites where chromaffin tissue is not usually found. Some tumors show gross local invasion and recurrence, which may indeed kill the patient, but this does not necessarily associate with metastatic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Ultrasound examination mainly manifested as round lowecho mass with clear boundaries, and some internal echoes were uneven. CDFI showed speckled and striped blood flow signals within the mass (9). Previous study showed that BPGs were solitary, and 40% were located on the dome.…”
Section: Ultrasound Manifestationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Ultrasound examination mainly manifested as round lowecho mass with clear boundaries, and some internal echoes were uneven. CDFI showed speckled and striped blood flow signals within the mass (9). Previous study showed that BPGs were solitary, and 40% were located on the dome.…”
Section: Ultrasound Manifestationsmentioning
confidence: 80%
“…BPG is a rare tumor derived from the medullary tissue of the bladder wall sympathetic nervous system, which mostly occurs in the submucosa and muscularis mucosa (8). The majority of BPGs are benign, and the only absolute criterion for malignancy is the presence of metastases at sites where chromaffin tissue is not usually found (9). BPGs could be divided into functional and non-functional according to catecholamine content and active degree of release (8).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these paragangliomas are occasionally diagnosed incorrectly; thus, surgeons are unprepared and the surgery to remove paragangliomas may result in an intraoperative hypertensive crisis and increase the mortality rate (7). Several reviews have been published on paragangliomas of the urinary bladder (8,9); however, non-functioning paragangliomas of the urinary bladder have rarely been reported (10). The present study reports the case of an asymptomatic patient with non-functioning paraganglioma of the bladder, which was detected as a mass on urinary ultrasonography scans.…”
Section: Introductionmentioning
confidence: 99%
“…Paraganglioma may be confused with nested variant urothelial carcinoma because of their nest structures; therefore, zellballen structures in the histopathological examination are very helpful in diagnosis. The majority of tumors have the characteristic zellballen pattern consisting of nest structures separated by thin fibrovascular septa at least focally [4].…”
Section: Discussionmentioning
confidence: 99%